1997
DOI: 10.1146/annurev.immunol.15.1.351
|View full text |Cite
|
Sign up to set email alerts
|

Redox Regulation of Cellular Activation

Abstract: Growing evidence has indicated that cellular reduction/oxidation (redox) status regulates various aspects of cellular function. Oxidative stress can elicit positive responses such as cellular proliferation or activation, as well as negative responses such as growth inhibition or cell death. Cellular redox status is maintained by intracellular redox-regulating molecules, including thioredoxin (TRX). TRX is a small multifunctional protein that has a redox-active disulfide/dithiol within the conserved active site… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
715
0
15

Year Published

1999
1999
2010
2010

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 1,026 publications
(740 citation statements)
references
References 83 publications
10
715
0
15
Order By: Relevance
“…6 Although the precise mechanism of thioredoxin secretion is still not clarified, plasma levels of human thioredoxin are the response against oxidative stress. 7 There is a possibility that plasma thioredoxin levels were elevated by the inflammatory response against the oxidative stress in patients with AMI in the present study.…”
Section: Discussionmentioning
confidence: 62%
“…6 Although the precise mechanism of thioredoxin secretion is still not clarified, plasma levels of human thioredoxin are the response against oxidative stress. 7 There is a possibility that plasma thioredoxin levels were elevated by the inflammatory response against the oxidative stress in patients with AMI in the present study.…”
Section: Discussionmentioning
confidence: 62%
“…TRX is a 12 kDa protein with a highly conserved redox-active dithiol/disulfide active site sequence, Cys 32 -Gly-Pro-Cys 35 , which, together with GSH constitutes the major redox-regulating molecules that maintain cellular redox balance [16,17]. Several studies have demonstrated protective effect of TRX in diseases associated with increased oxidative stress such as post-ischaemic reperfusion injury, adriamycin-induced cardiotoxicity and diabetic nephropathy [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…TRX has been shown to protect cells from oxidative stress and apoptosis [15][16][17]. Several studies have shown that TRX is induced by various types of stress, such as viral infection, ischaemic insult, ultraviolet light, X-ray irradiation and H 2 O 2 [18]. TRX acts as a scavenger of ROS and can repair proteins oxidised by ROS [13,18].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that TRX is induced by various types of stress, such as viral infection, ischaemic insult, ultraviolet light, X-ray irradiation and H 2 O 2 [18]. TRX acts as a scavenger of ROS and can repair proteins oxidised by ROS [13,18]. In-vitro studies have demonstrated that TRX has a protective effect against the cytotoxicity of ROS [18].…”
Section: Introductionmentioning
confidence: 99%